The Expression of Ferroptosis-Related Genes in Hepatocellular Carcinoma and Their Relationships With Prognosis - Li H; Hu X; Wang L; Gu X; Chen S; Tang Y; Chen Y; Chen J; Yuan Z; Wang Y (Journal of Hepatocellular Carcinoma)
Hongxu Li,1,* Xinyue Hu,1,* Li Wang,2,* Xiangran Gu,1 Shibin Chen,1 Yixuan Tang,1 Yuan Chen,2 Jin Chen,2 Zhengrong Yuan,1 Yajie Wang2 1College of Biological Sciences and Technology, Beijing Forestry University, Beijing, People’s Republic of China; 2Department of Clinical Laboratory, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhengrong Yuan; Yajie Wang, Email zryuan@bjfu.edu.cn; wangyajie@ccmu.edu.cnBackground: Ferroptosis, a form of cell death discovered in recent years, is expected to provide new targets for the diagnosis and treatment of hepatocellular carcinoma (HCC) through further research.Methods: Based on data from The Cancer Genome Atlas (TCGA), we screened HCC-associated genes from 259 candidate genes in the FerrDb database. The screened genes were subjected to differential expression analysis, survival analysis, correlation analysis with clinical data, and univariate and multivariate Cox regression analysis. The results were validated with the Gene Expression Profiling Interactive Analysis 2 (GEPIA2) database and the Human Protein Atlas (HPA) database, and signaling pathways were analyzed with the Gene Set Enrichment Analysis (GSEA) enrichment analysis. Human normal hepatocytes and different liver cancer cell lines were used to verify the expression levels of genes, using quantitative reverse transcription PCR (RT-qPCR).Results: Eight ferroptosis-related genes were finally selected, including ACSL3, ASNS, CHMP5, MYB, PCK2, PGD, SLC38A1, and YY1AP1. The expression of eight genes except PCK2 was significantly correlated with a lower survival rate of HCC, and the expression of PCK2 showed a correlation with a higher survival rate of HCC. The expression of all eight genes was also correlated with clinical traits. GSEA enrichment analysis obtained many pathways such as apoptosis, endocytosis, pathways in cancer, Wnt signaling pathway, primary bile acid biosynthesis, and fatty acid metabolism pathway.Conclusion: The ACSL3, ASNS, CHMP5, MYB, PCK2, PGD, SLC38A1, and YY1AP1 genes may become markers and new targets for early diagnosis and prognostic assessment of HCC.Keywords: hepatocellular carcinoma, ferroptosis, prognostic markers, TCGA, FerrDb